Human papillomavirus in the setting of immunodeficiency: Pathogenesis and the emergence of next-generation therapies to reduce the high associated cancer risk - Hewavisenti, Rehana V.; Arena, Joshua; Ahlenstiel, Chantelle L.; Sasson, Sarah C. (Frontiers in Immunology, 2023)
Human papillomavirus (HPV), a common sexually transmitted virus infecting mucosal or cutaneous stratified epithelia, is implicated in the rising of associated cancers worldwide. While HPV infection can be cleared by an adequate immune response, immunocompromised individuals can develop persistent, treatment-refractory, and progressive disease. Primary immunodeficiencies (PIDs) associated with HPV-related disease include inborn errors of GATA, EVER1/2, and CXCR4 mutations, resulting in defective cellular function. People living with secondary immunodeficiency (e.g. solid-organ transplants recipients of immunosuppression) and acquired immunodeficiency (e.g. concurrent human immunodeficiency virus (HIV) infection) are also at significant risk of HPV-related disease. Immunocompromised people are highly susceptible to the development of cutaneous and mucosal warts, and cervical, anogenital and oropharyngeal carcinomas. The specific mechanisms underlying high-risk HPV-driven cancer development in immunocompromised hosts are not well understood. Current treatments for HPV-related cancers include surgery with adjuvant chemotherapy and/or radiotherapy, with clinical trials underway to investigate the use of anti-PD-1 therapy. In the setting of HIV co-infection, persistent high-grade anal intraepithelial neoplasia can occur despite suppressive antiretroviral therapy, resulting in an ongoing risk for transformation to overt malignancy. Although therapeutic vaccines against HPV are under development, the efficacy of these in the setting of PID, secondary- or acquired- immunodeficiencies remains unclear. RNA-based therapeutic targeting of the HPV genome or mRNA transcript has become a promising next-generation therapeutic avenue. In this review, we summarise the current understanding of HPV pathogenesis, immune evasion, and malignant transformation, with a focus on key PIDs, secondary immunodeficiencies, and HIV infection. Current management and vaccine regimes are outlined in relation to HPV-driven cancer, and specifically, the need for more effective therapeutic strategies for immunocompromised hosts. The recent advances in RNA-based gene targeting including CRISPR and short interfering RNA (siRNA), and the potential application to HPV infection are of great interest. An increased understanding of both the dysregulated immune responses in immunocompromised hosts and of viral persistence is essential for the design of next-generation therapies to eliminate HPV persistence and cancer development in the most at-risk populations.